Functional map of the alpha subunit of Escherichia coli RNA polymerase: two modes of transcription activation by positive factors. - Igarashi, K (1991)
The role of the alpha subunit of Escherichia coli RNA polymerase in transcription activation by positive factors was investigated using two reconstituted mutant RNA polymerases (containing C-terminally truncated alpha subunits) and three positive factors [the cAMP receptor protein (CRP), OmpR, and PhoB]. The mutant RNA polymerases did not respond to transcription activation by activator proteins that bind upstream of the respective promoters. Transcription by these mutant enzymes was, however, activated in the cases where activators bind to target sites that overlap the promoter -35 region. Two different mechanisms are proposed for the positive control of transcription by activator proteins, one requiring the C-terminal domain of the alpha subunit, and the other not requiring it.